Bud endodormancy – a familiar but still unknown key adaptive trait in extratropical woody plants - Zhang, Rui; Hänninen, Heikki; Wu, Jiasheng; Bhalerao, Rishikesh P. (Frontiers in Plant Physiology, 2023)
In autumn, the buds of extratropical trees are in a state of endodormancy, since regardless of the prevailing environmental conditions, growth cannot be activated in these buds because the dormancy is caused by physiological factors in the buds. In natural conditions the growtharresting physiological factors are removed by prolonged exposure to low chilling temperatures. This phenomenon is a key adaptive trait, for it prevents 'false spring', i.e., untimely bud burst during mild spells in autumn and winter, which would lead to cold damage during subsequent cold periods. Traditionally, endodormancy and the chilling requirement have been important in practical horticulture, as cultivars with low and high chilling requirements have been bred for locations in warm and cool climates, respectively.More recently, endodormancy and the chilling requirement have become major research 2 themes in climate change studies where climatic change impacts are assessed by means of process-based tree phenology models. The dormancy phenomenon has been studied thoroughly at the whole-tree level for a hundred years, and several genes and genetic pathways involved have recently been identified in tree species such as hybrid aspen, apple, and pear. There is an urgent need, however, to integrate molecular physiological studies with modelling studies so as to understand the impact of climate change on the regulation of dormancy. To that end, we shall provide an overview of bud endodormancy research.